Pengaruh Hasil Investasi, Pendapatan Premi, Beban Klaim, dan Beban Operasional Terhadap Laba Perusahaan Asuransi Yang Terdaftar Di bursa Efek Indonesia - Muammar Khaddafi; Agung (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2021)
This study aims to examine the effect of investment returns, premium income, claim expenses, and operating expenses on the profits of insurance companies listed on the Indonesia Stock Exchange (IDX) in 2019-2020. The sample selection technique used a saturated sample and 16 insurance companies listed on the Indonesia Stock Exchange (IDX) were used in this study. This study uses a balance panel with 32 observations and estimates (fixed effect model). The results of this study found that the investment return variable has no effect and is not significant on profit. Meanwhile, premium income has a significant negative effect on profit. Variables of claims expense and operating expense have a positive and significant im